The Effect of Industrial Work Practice Experience and Entrepreneurship Education on Interest in Entrepreneurship Using Social Media as a Moderating Variable - Kustiadi Basuki; Sherlina Gratia (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the effect of industrial work practice experience and entrepreneurship education on entrepreneurial interest and the use of social media as a moderating variable. This research model is a quantitative study with a sample of 200 people obtained through a questionnaire in google form distributed on social media. The results obtained by the research show that entrepreneurship education and the use of social media have a positive and significant effect on interest in entrepreneurship, but the use of social media cannot be a moderating variable on the effect of industrial work practice experience on interest in entrepreneurship.